Cross‐talk between a regulatory small RNA, cyclic‐di‐GMP signalling and flagellar regulator FlhDC for virulence and bacterial behaviours. (14th October 2015) - Yuan, Xiaochen; Khokhani, Devanshi; Wu, Xiaogang; Yang, Fenghuan; Biener, Gabriel; Koestler, Benjamin J.; Raicu, Valerica; He, Chenyang; Waters, Christopher M.; Sundin, George W.; Tian, Fang; Yang, Ching‐Hong
Summary: D ickeya dadantii is a globally dispersed phytopathogen which causes diseases on a wide range of host plants. This pathogen utilizes the type III secretion system (T3SS) to suppress host defense responses, and secretes pectate lyase (Pel) to degrade the plant cell wall. Although the regulatory small RNA (sRNA) RsmB, cyclic diguanylate monophosphate (c‐di‐GMP) and flagellar regulator have been reported to affect the regulation of these two virulence factors or multiple cell behaviours such as motility and biofilm formation, the linkage between these regulatory components that coordinate the cell behaviours remain unclear. Here, we revealed a sophisticated regulatory network that connects the sRNA, c‐di‐GMP signalling and flagellar master regulator FlhDC. We propose multi‐tiered regulatory mechanisms that link the FlhDC to the T3SS through three distinct pathways including the FlhDC‐FliA‐YcgR3937 pathway; the FlhDC‐EcpC‐RpoN‐HrpL pathway; and the FlhDC‐ rsmB ‐RsmA‐HrpL pathway. Among these, EcpC is the most dominant factor for FlhDC to positively regulate T3SS expression.